Maintainance of diagnostic Laboratory during pandemic emergency (SARS-CoV-2) in a Small Hospital: Laboratory medicine in the COVID-19 era - Sammartano, Antonino; Testa, Giulia; Ippolito, Luigi (Acta Biomedica Atenei Parmensis, 2022)
.